Is Fiscal Decentralization a means to Poverty Reduction? - Kartika, Metasari; Hendarmin, Hendarmin; Ramadhan, Muhammad Rheza (EcceS: Economics, Social, and Development Studies, 2023)
The number of poor people in West Kalimantan is still in the second highest position among the provinces in Kalimantan the poverty level in six districts is above the national poverty level. The research aims to determine the impact of fiscal decentralization which is proxied by the General Allocation Fund, education which is proxied by the Average Years of Schooling, and Economic Growth on the number of poor people in the District/City of West Kalimantan Province. This research uses secondary data from 2010-2022. The novelty of this research is the use of the General Allocation Fund variable which is regional income from central transfers. Previous researchers have rarely used the General Allocation Fund variable to see the relationship between transfer funds and poverty alleviation efforts in West Kalimantan Province. In the future, more attention will be paid to the allocation and use of the General Allocation Fund so that it will have an impact on overcoming poverty and using quantitative analysis with panel data regression method, Fixed Effect Model (FEM) approach. The research results found that the general allocation fund variable had a significant and positive effect on the number of poor people. the variable average length of schooling has a significant and negative effect on the number of poor people, and economic growth has an insignificant and positive effect on the number of poor people in the District/City of West Kalimantan Province. The results of this research are the basis for consideration of the West Kalimantan Provincial government policy to eradicate poverty which is carried out thoroughly and comprehensively through the government's role in the form of strengthening fiscal decentralization and improving economic performance in each Regency/City area of ​​West Kalimantan Province.